Effects of neuroticism-anxiety and sociability personality traits on the relationship between testosterone and risk propensity in finance - Ferjančič, Urša (Economic and business review, 2024)
Risky fnancial decisions, defined as rational calculations between expected risk and reward, are subject to various psychological and neurobiological mechanisms. In this context, the relationship between testosterone levels and risk propensity has been investigated, but the results are inconsistent. Here, the effects of some personality traits, neuroticism-anxiety and sociability, on the relationship between testosterone levels and risk propensity were examined in decisions under risk (GDT) and under uncertainty (BART). In a mixed-sex sample of 100 graduate students and experienced decision makers, we found that basal testosterone levels were positively correlated with risk propensity for decisions under risk in males with low neuroticism-anxiety scores, whereas they were negatively correlated with risk propensity for decisions under risk in males with high neuroticism-anxiety scores. However, they were not correlated in (i) decisions under uncertainty in males, independent of neuroticism-anxiety, (ii) decisions under risk or under uncertainty in males, independent of sociability, and (iii) decisions under risk or under uncertainty in females, independent of sociability and neuroticism-anxiety. These results indicate that neuroticism-anxiety, but not sociability, may affect the relationship between testosterone levels and risk propensity only in decisions under risk and only in males, and provide evidence for the complexity of this relationship in males.
Keywords: analize; decision making; finance; odločanje; risk; tveganje